Strategic Planning Adoption in Public Organization in Indonesia - Yosandi, Yosi; Wijaya, Andy Fefta; Nuh, Mohammad (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2017)
Strategic planning in public sector in Indonesia has been fully supported by the regulations, but the implementation has not been applied properly. Meanwhile, empirical evidence related to what extent strategic planning has been adopted by public sector in Indonesia in order to support the critique that a strategic planning affects what an organization is, what it does and why it does it is still limited. Under qualitative method, the study tries to explore how far strategic planning principles have been adopted in public organization by using case study in Directorate of Land and Forest Fire Controlling, Directorate General of Climate Change Controlling, Ministry of Environment and Forestry. The study focuses on analyzing the process of strategic plan arrangement. Research result shows that strategic planning principles haven’t been adopted properly on the arrangement of strategic plan document of Directorate of Forest and Land Fire Controlling (PKHL). There are several important points to be noticed, are: stakeholder analysis hadn’t been used properly and the TOWS matrix wasn’t used to formulate strategy development.